2020
DOI: 10.1080/19424396.2020.12222558
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Medicine and Technology in Shaping the Future of Oral Health

Abstract: chair of and a professor of biomedical sciences at the University of the Pacific, Arthur A. Dugoni School of Dentistry. His research is currently focused on the immune response to periodontal pathogens. Arthur A. Dugoni, DDS, MSD dean emeritus, professor of orthodontics and senior executive for development at the University of the Pacific, Arthur A. Dugoni School of Dentistry. In 2004, he became the first and only person in the United States or Canada to have a dental school named in his honor while holding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In addition, digital health technologies can improve the health literacy of community members regarding oral hygiene and can advertise and promote a variety of appropriate interventions necessary in different periods of life, such as special education programs for children, mothers, and older adults [ 57 ]. In addition, new knowledge and technologies can potentially create tremendous changes in diagnosing and managing oral and dental diseases [ 8 , 58 ]. In addition, nanotechnology in dentistry has received serious attention in recent years [ 59 ], and nanotechnology is practical in various fields of dentistry, from diagnosis to prevention and treatment [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, digital health technologies can improve the health literacy of community members regarding oral hygiene and can advertise and promote a variety of appropriate interventions necessary in different periods of life, such as special education programs for children, mothers, and older adults [ 57 ]. In addition, new knowledge and technologies can potentially create tremendous changes in diagnosing and managing oral and dental diseases [ 8 , 58 ]. In addition, nanotechnology in dentistry has received serious attention in recent years [ 59 ], and nanotechnology is practical in various fields of dentistry, from diagnosis to prevention and treatment [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the burden of diseases in 2017 have indicated that oral diseases affect more than half of the world’s population [ 4 , 5 ].Various studies have confirmed the relationship between oral and dental health and the physical, mental, and social aspects of health, highlighting its importance as one of the essential components of public health [ 7 ]. Taking care of oral and dental health is a gateway for early diagnosis and prevention of many oral as well as many systemic diseases [ 8 ]. Based on the common risk factors approach, oral diseases are considered a risk factor in developing or increasing the severity of systemic conditions [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The burden of oral diseases primarily stems from complex conditions involving the interaction of multiple genes with environmental factors [ 73 ]. With the ever-evolving scientific knowledge and technologies, the greatest challenge that the dental fraternity currently faces is implementing and enhancing omics literacy, promoting individual and population oral health, and reducing disparities [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Technological advances in medicine and dentistry bring numerous advantages that have a positive impact on maintaining or achieving oral health, but also certain problems and doubts. The use of AI in dentistry has several advantages, including ( 137 , 138 ):…”
Section: Advantages and Disadvantages Of Artificial Intelligence In D...mentioning
confidence: 99%